Bacterial Vaginosis in Pregnancy as a Risk Factor for Obstetric Complications – Analysis of Current Evidence and Management Strategies - Krupa, Martyna; Kulczykowska , Wiktoria; Krzyśkowska, Sylwia; Kozińska, Anna; Krukowska, Kamila; Krawiec, Laura; Paszt, Zuzanna (Quality in Sport, 2026)
Background. Bacterial vaginosis (BV) is a common condition in pregnancy associated with an increased risk of adverse obstetric outcomes, particularly preterm birth. However, the underlying mechanisms and the effectiveness of screening and treatment strategies remain uncertain. Aim. This review aimed to evaluate the role of bacterial vaginosis as a risk factor for obstetric and neonatal complications and to assess current approaches to its diagnosis and management. Material and methods. A narrative literature review was conducted using the PubMed database with predefined keywords related to bacterial vaginosis, pregnancy, and obstetric outcomes. Results. The available evidence indicates that BV is associated with an increased risk of preterm birth, low birth weight, premature rupture of membranes, and selected neonatal complications. BV reflects a disruption of the vaginal microbiome characterized by reduced Lactobacillus dominance and increased microbial diversity, which may promote inflammatory responses and ascending infection. Despite strong epidemiological associations, antibiotic treatment during pregnancy does not consistently reduce adverse outcomes, particularly in low-risk populations. Variability in diagnostic methods further contributes to inconsistent findings. Conclusions. Bacterial vaginosis should be considered an important risk marker rather than a direct causal factor in all cases. Routine screening and uniform treatment strategies do not provide consistent clinical benefit. Future approaches should focus on individualized, risk-based management and microbiome-oriented strategies.